Newest data on fluoroquinolone resistance mechanism of Shigella flexneri isolates in Jiangsu Province of China - Qin, Tingting (Antimicrob Resist Infect Control, 2017)
BACKGROUND: To determine the prevalence, antimicrobial susceptibility patterns and related presence of mutations in quinolone resistance-determining region (QRDR) genes and plasmid-mediated quinolone resistance (PMQR) among Shigella flexneri isolates obtained from Jiangsu Province, China. METHODS: A total of 400 Shigella flexneri clinical isolates collected during 2012–2015 were identified by biochemical and serological methods, and the antimicrobial susceptibility pattern was evaluated using the disc-diffusion method. PCR and DNA sequencing were accomplished to identify mutations in gyrA, gyrB, parC and parE, and the presence of qnrA, qnrB, qnrC, qnrD, qnrS, qepA and aac(6′)-Ib-cr genes were also detected. RESULTS: Of all the Shigella flexneri, 75.8% were resistant to nalidixic acid, and 37.0% were categorized as norfloxacin resistant. Overall, 75.5% of isolates possessed gyrA mutations (Ser83Leu, Asp87Gly/Asn and His211Tyr), while 84.3% had parC mutations (Ser80Ile, Ala81Pho, Gln91His and Ser129Pro). The most prevalent point mutations in gyrA and parC were Ser83Leu (75.5%, 302/400) and Ser80Ile (74.5%, 298/400), relatively. Besides, the Gln517Arg alternation in gyrB was detected in 13 S. flexneri isolates and no mutations were identified in parE. PMQR determinations of qnrB, qnrS and aac(6′)-Ib-cr were detected among 16 strains (4.0%). CONCLUSIONS: The results presented here show that fluoroquinolone resistance in these clinical isolates result from mutations in chromosome, besides, despite the low prevalence of PMQR determinants in Jiangsu, it is essential to continue surveillance PMQR determinants in this area.